Self-tuning pid based navigation for autonomous mobile robot - R Sivam, Saravanakumar (2021)
The aim of this project is to design a self-tuning PID control system for an autonomous mobile robot. Then run the simulation of the system designed to test the performance of the controller system. This self-tuning PID controller is designed for the robot PIONEER 3D-X. First, the robot's kinematic and dynamic model was obtained by refer to journal. Designed the mathematical STC PID controller model with mathematical calculation. This PID controller is correlated with pole-assignment technique of self-tuning method. Pole-Assignment Control Method is an indirect self-tuning method that built the controller function based on the device parameter. This STC approach is the approach for controller design, by setting a control parameter, to locate the closed loop system poles at stable position in s-plane. Conventional PID controller were designed and implemented in robot model in order to result comparison. The conventional PID controller designed using Auto-Tuning technique. MATLAB Simulink was used in this project to run the simulation of the models designed. Reference trajectory was insert as input signal to the robot model and actual trajectory was evaluated. Analysis about the actual trajectory and variables of both STC and conventional PID controller system. Response graph obtained and used in evaluation of the system.